Home visits in primary care: Differences among professional categories and health macro-regions - Leandro M Diniz; Gabriela A C. Rhodes; Mauro H.N G. Abreu; Ana C Borges-Oliveira; Loliza L.F H. Chalub (Indian Journal of Dental Research, 2020)
Context: Home visit is a modality of health care that is expanding in Brazil and in the world. Public and private services have invested in the implementation of this type of assistance. It happens due to its potential to transform the model of care, highlighting the work quality of the primary health care teams. Aims: To analyze house call rates in primary care in the Brazilian public healthcare system according to professional categories and health macro-regions in the state of Minas Gerais, southeast region of Brazil. Settings and Design: An ecological study that used as the information source the production data from the Primary Care Information System (2010 to 2015). Methods and Materials: House call rates (per 3000 inhabitants) by primary care professionals constituted the response variable. The independent variables were professional categories and the 13 health macro-regions of the state. Statistical Analysis Used: The data were analyzed using the Mann-Whitney test. Results: A total of 26,932,463 house calls were performed in the period, but the number of visits in 2015 was significantly lower compared to 2010. Significantly higher house call rates were found for some professional categories (mid-level professionals and nurses) and significant differences were found among the macro-regions (P < 0.05). Conclusions: The profile of house calls by primary care professionals revealed the constant presence of this care modality, but the distribution of these visits is uneven among the different professional categories and macro-regions of the state.